Estudio de factibilidad para el montaje de una pasteurizadora con distribución al jarreo para la Asociación de Ganaderos de Calarcá (2016)
The research about the distribution company feasibility of pasteurizer products shows the strategic solution given the government requirements, changing threats for new business opportunities, adding value to the product and involving producers, consumers and the environment with favorable results.